A novel anatomo-physiologic high-grade spondylolisthesis model to evaluate L5 nerve stretch injury after spondylolisthesis reduction - Ishak, Basem; Pierre, Clifford A.; Ansari, Darius; Lachkar, Stefan; Glinski, Alexander von; Unterberg, Andreas; Oskouian, Rod J.; Chapman, Jens R. (Neurosurgical review, 2022)
L5 nerve palsy is a well-known complication following reduction of high-grade spondylolisthesis. While several mechanisms for its occurrence have been proposed, the hypothesis of L5 nerve root strain or displacement secondary to mechanical reduction remains poorly studied. The aim of this cadaveric study is to determine changes in morphologic parameters of the L5 nerve root during simulated intraoperative reduction of high-grade spondylolisthesis. A standard posterior approach to the lumbosacral junction was performed in eight fresh-frozen cadavers with lumbosacral or lumbopelvic screw fixation. Wide decompressions of the spinal canal and L5 nerve roots with complete facetectomies were accomplished with full exposure of the L5 nerve roots. A 100% translational slip was provoked by release of the iliolumbar ligaments and cutting the disc with the attached anterior longitudinal ligament. To evaluate the path of the L5 nerves during reduction maneuvers, metal bars were inserted bilaterally at the inferomedial aspects of the L5 pedicle at a distance of 10 mm from the midpoint of the L5 pedicle screws. There was no measurable change in length of the L5 nerve roots after 50% and 100% reduction of spondylolisthesis. Mechanical strain or displacement during reduction is an unlikely cause of L5 nerve root injury. Further anatomical or physiological studies are necessary to explore alternative mechanisms of L5 nerve palsy in the setting of high-grade spondylolisthesis correction, and surgeons should favor extensive surgical decompression of the L5 nerve roots when feasible.
Gesehen am 27.07.2023
Online veröffentlicht am 29 December 2021